"I hear America singing" : folk music and national identity - Donaldson, Rachel Clare (Temple University Press, 2014)
Folk music is more than an idealized reminder of a simper past. It reveals a great deal about present-day understandings of community and belonging. It celebrates the shared traditions that define a group or nation. In America, folk music--from African American spirituals to English ballads and protest songs--renders the imagined community more tangible and comprises a critical component of our diverse national heritage. In ""I Hear America Singing, "" Rachel Donaldson traces the vibrant history of the twentieth-century folk music revival from its origins in the 1930s through its end in the lat.